Trend and future of infant mortality in Pakistan - Zartashia Shabbir; Anila Riaz; Fiaz Ahmad; Muhammad Imran shakoor (Journal of University Medical & Dental College, 2022)
In South Asia, Pakistan is contributing to the highest childhood mortality, including infant mortality. Child mortality has been declined globally, but Pakistan is still struggling and far behind the targets of Sustainable Development Goals. There are several reasons behind high childhood mortality, including socioeconomic determinants and a lack of effective implementation of health-related policies, particularly in primary health care settings. In the present study, we use the stochastic univariate models to uncover the trend of infant mortality by using more than half of the century data from 1960-2017. The secondary data on infant mortality rate from 1960 to 2017 was extracted from World Bank Dataset. Descriptive and time series analysis were applied by using the programming language R. The median infant mortality rate was 109 per 1,000 live births, whereas a higher mortality rate (189.8/1000) was reported in 1960. A gradual decline in infant mortality rates is experienced every year. The mortality rate went down below 100/1,000 live births from 1993 and remained 61.2/1,000 in 2017. ARIMA (1, 2, 2) is an adequate forecasting model selected by using the Auto ARIMA function with a root mean square error is 0.1006. Five years ahead forecast is obtained and yielded that infant mortality rate is expected to remain in 2018 [59.54, C.I (59.34 - 59.73)], 2019 [57.93, C.I (57.47 - 58.40)], 2020 [56.39, C.I (55.48 - 57.30)], 2021 [54.90, C.I (53.35 - 56.45)] and 2022 [53.47, C.I (51.05 - 55.88)]. The decreasing trend is expected in the infant mortality rate in Pakistan.